2023
DOI: 10.1039/d3ta00901g
|View full text |Cite
|
Sign up to set email alerts
|

Metal-free 3D donor–acceptor COF with low exciton binding for solar fuel production based on CO2reduction

Abstract: Recent upsurge in developing organic materials as photocatalyst for CO2 reduction is stemmed from low cost, tunable band gap and high selectivity compared to inorganic semiconductors. Herein, we have reported...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 80 publications
0
16
0
Order By: Relevance
“…Since the HOMO reduction potential is more positive than the reduction potential of O 2 /H 2 O couple, the system can be active for the CO 2 reduction in water . Moreover, the room-temperature CO 2 adsorption–desorption isotherm of Zr-MBA-TET-Re-MOF depicted significant CO 2 uptake (19.8 cm 3 g –1 ), favoring the reduction reaction by increasing the CO 2 diffusibility into the system (Figure i) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the HOMO reduction potential is more positive than the reduction potential of O 2 /H 2 O couple, the system can be active for the CO 2 reduction in water . Moreover, the room-temperature CO 2 adsorption–desorption isotherm of Zr-MBA-TET-Re-MOF depicted significant CO 2 uptake (19.8 cm 3 g –1 ), favoring the reduction reaction by increasing the CO 2 diffusibility into the system (Figure i) …”
Section: Resultsmentioning
confidence: 99%
“…28 Moreover, the room-temperature CO 2 adsorption−desorption isotherm of Zr-MBA-TET-Re-MOF depicted significant CO 2 uptake (19.8 cm 3 g −1 ), favoring the reduction reaction by increasing the CO 2 diffusibility into the system (Figure 3i). 60 Photocatalytic CO 2 Reduction Reaction. Photocatalytic CO 2 reduction has been performed with Zr-MBA-TET-Re-MOF in water with continuous light illumination.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Covalent organic framework (COF) materials are a new type of crystalline porous material which are ingeniously constructed with organic molecules linked by strong covalent bonds (CN, CC, B–O, C–O, etc.). Due to their ultralow density, high crystallinity, high surface area, and ordered accessible porous structures, COF materials have been applied in many fields, such as gas storage/separation, drug delivery, fluorescence sensing, proton conduction, catalysis, and so on. Two-dimensional (2D) COF materials are a type of COF material which are constructed by π–π stacking of the adjacent COF layers. The extensive π-electron delocalization effect of the 2D COF materials facilitates charge transfer in the materials, which is beneficial for catalytic reactions over the materials.…”
Section: Introductionmentioning
confidence: 99%
“…Exciton binding energy ( E b ), as an important parameter to evaluate excitonic effects, indicates the strength of Coulomb interaction between electrons and holes . Recent notable contributions have confirmed that building donor–acceptor (D–A) systems can accelerate the dissociation of excitons due to the existence of polarized electric fields. , Nonetheless, in most CMPs with D–A dyads, backward charge recombination of excitons also occurs simultaneously in intramolecular charge transfer due to the strong exciton effect, seriously affecting the production of free charge carriers . Thus, it is necessary to minimize the exciton effect to enhance photocatalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…37,38 Nonetheless, in most CMPs with D−A dyads, backward charge recombination of excitons also occurs simultaneously in intramolecular charge transfer due to the strong exciton effect, seriously affecting the production of free charge carriers. 39 Thus, it is necessary to minimize the exciton effect to enhance photocatalytic performance. To this end, we and other groups have indicated that extending πconjugated delocalization to increase the migrating distance of charge carriers can efficiently promote intramolecular charge separation and transfer by modulating exciton behaviors (Figure 1a).…”
Section: ■ Introductionmentioning
confidence: 99%